The mitigative effect of ovotransferrin-derived peptide IQW on DSS-induced colitis via alleviating intestinal injury and reprogramming intestinal microbes - Chai, Yajuan; Ding, Sujuan; Jiang, Lihong; Wang, Shuangshuang; Yuan, Xiangnan; Jiang, Hongmei; Fang, Jun (Frontiers in Nutrition, 2022)
Inflammatory bowel disease (IBD) is a chronic disease with multiple complications during its development, and it is difficult to cure. The aim of this study was to evaluate the alleviating effect of different concentrations of the bioactive peptide IQW (Ile-Gln-Trp) on dextran sodium sulfate (DSS) induced colitis in mice. For this study, we randomly divided 56 ICR mice into seven groups: (I) Control group (CON), (II) Dextran sodium sulfate treatment group (2.5% DSS), (III) IQW-DSS (20 μg/mL) treatment group, (IV) IQW-DSS (40 μg/mL) treatment group, (V) IQW-DSS (60 μg/mL) treatment group, (VI) IQW-DSS (80 μg/mL) treatment group, and (VII) IQW-DSS (100 μg/mL). The results showed that IQW at 60 μg/mL alleviated body weight loss, improved the liver index (p<0.05), and improved histomorphological and pathological changes in the colon compared to the DSS-treated group. IQW at 60 μg/mL and IQW at 80 μg/mL modified intestinal microbial disorders. In addition, IQW at 60 μg/mL significantly increased butyric acid levels and decreased valeric acid levels, while IQW at 80 μg/mL significantly increased Isobutyric acid and Isovaleric acid levels. Hence, IQW at a concentration of 60 μg/mL alleviates DSS-induced colitis by enhancing the body’s anti-inflammatory ability and regulating intestinal flora and metabolic changes. In the above context, IQW at 60 μg/mL could be a potential candidate for IBD prevention and treatment.